DETERMINATION OF THE RISKS OF INFERTILITY IN WOMEN WITH THYROID PATHOLOGY AND HYPOANDROGENIC OVARIAN DYSFUNCTION - Semeniuk, L.М.; Yuzvenko, T.Y.; Borodkin, H.O.; Kryzhanovskaya, O.I. (World of Medicine and Biology, 2020)
The purpose of the study was to determine the effect of thyroperoxidase antibody levels on the fertility of women with sexual dysfunction and reduced ovarian androgen levels. A study of the risks of infertility in women with pathology of the thyroid gland based on the analysis of the results of hormonal tests and the development of recommendations for planning a pregnancy in conditions of hypoandrogenic ovarian dysfunction. The presence of clinically significant levels of antibodies to thyroperoxidase in young and middle-aged women with sexual dysfunction has been shown to adversely affect the early stages of folliculogenesis. This factor indicates a risk of decreased steroid-producing ovaries and the development of susceptibility to infertility. It is desirable for women with clinically significant levels of antibodies to thyroperoxidase to plan their pregnancy at an earlier reproductive age (18-25 years), because at this time the optimal conditions for fertility are maintained. For women with clinically low levels of antibodies to thyroperoxidase, pregnancy planning is more appropriate in middle reproductive age.
Keywords: infertility; antibodies; androgen deficiency